Ekstrakurikuler Gitar Elektrik di SMA Negeri 2 Kota Bengkulu - Muhammad Andrian Marandika; Irdhan Epria Darma Putra (EDUMUSIKA, 2024)
This research aims to describe the extracurricular implementation of electric guitar. This research is classified as qualitative research and the method used is descriptive analysis. The research instrument is the researcher himself as the main instrument. Data collection was carried out through the stages of literature study, observation, interviews, and audio and video recording. The conclusion from the results of this research is that the application of the group discussion method and the drill method can be used in electric guitar extracurricular activities at SMA Negeri 2 Bengkulu City because they are very effective in practicing electric guitar extracurricular activities for students, as well as implementing extracurricular activities using materials Fingering, picking and scale techniques are appropriate because the material studied is basic material in playing electric guitar properly and correctly so that students know the basic techniques for playing electric guitar and can improve their individual abilities. The author also observes that developing the trainer's learning is very important, such as adding variety to the method of teaching electric guitar to students. One way is to introduce video screenings or live performances from famous guitar players as an alternative to encourage student motivation to improve their skills. Evaluation activities are carried out with the aim of identifying the extent of students' abilities and weaknesses, so that they can improve themselves more diligently.